Peningkatan Pendidikan Karakter untuk Anak-Anak Pekerja Migran Indonesia di Penang, Malaysia - Andi Triyawan; Afni Regita Cahyani; Muhammad Ismail; Khusnul Mawarida; Salsa Nabila; Salsabilla Faturohma (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Children of Indonesian migrant workers in Penang Island, Malaysia face some challenges in accessing decent and sustainable education. This study aims to analyze efforts to improve basic competencies as a strategy to develop their scientific capacity. This study focuses on two main aspects in improving educational character, such as religious and national knowledge. Improving religious competencies is through learning Islamic values and worship practices. This aims to form a strong religious character in a multicultural environment. Furthermore, efforts to improve national competencies are implemented through educational history, nationalist values, and introduction to Indonesian culture so that children continue to have a sense of love for their homeland. The results refer to a systematic educational approach based on the needs of migrant worker children so that they can significantly improve their basic competencies. Therefore, education for migrant worker children does not only function as a means of transferring knowledge but as a strategy to strengthen their identity, social integration, and future opportunities either nationally and internationally.